عقد الوكالة المحفزة ودوره في تسيير المرافق الإقتصادية في الجزائر - شنوف, الطاهر (My University, 2023)
واجيت الإدارة العامة لمخدمة العامة في الج ا زئر العديد من النقائص والمشاكل التي أثرت عمى كفاءة وفعالية الخدمة العامة في تنفيذ مياميا ، حتى اضطرت الدولة لمبحث عن بدائل أخرى، تتمثل بشكل خاص في من خلال استخدام آلية تفويض 247 ، من خلال عدة / الخدمة العامة المنصوص عمييا في المرسوم الرئاسي 15 صيغ ، بما في ذلك عقد وكالة الحوافز، الذي يأخذ طابعًا خاصًا من حيث أن الإدارة نيابة عن السمطة المفوضة، ولا يقوم المفوض بذلك الحصول عمى المقابل المالي لتعريفات المستفيدين، بل يتم دفعو لو عمى شكل ا رتب محدد ، مع نسبة من حجم التداول المحقق في تشغيل الخدمة العامة مباشرة من السمطة العامة ، بالإضافة إلى الإنتاجية العلاوة وجزء من الأرباح، لإل ا زميا بتنفيذ منفعة عامة.The General Administration of the Public Service in Algeria faced many shortcomings and problems that affected the efficiency and effectiveness of the public service in carrying out its tasks, so that the state was forced to search for other alternatives, represented in particular by using the public service delegation mechanism stipulated in Presidential Decree 15/247, Through several formulas, including the incentive agency contract, which takes a special character in that the administration is on behalf of the delegated authority, and the delegate does not obtain the financial compensation for the tariffs of the beneficiaries, but rather it is paid to him in the form of a specific salary, with a percentage of the turnover The investigator in the operation of the public service directly from the public authority, in addition to the productivity bonus and part of the profits, to oblige it to carry out a public benefit
مذكرة ماستر
Keywords: الوكالة المحفزة ، الإدارة المفوضة ، المنافسة; motivating agency, delegated management, competition